Myths of doing business with Chinese - Chung, Mona (Henry Stewart Talks, 2013)
Outline of the presentation, Doing business with China, China business development, The uniqueness of China, Costs of doing business with China, Relationship building in doing business with China, Chinese economy, Power, Language